„Osobliwie muszę tu wyznać zrządzenie Boskie nad tobą Synu mój kochany, iż twoja najlepiej cię kochająca Matka, uniesiona często słabością rozumu swojego, biła cię i źle ci życzyła”. Choroba psychiczna w rodzinie w drugiej połowie XVIII wieku na przykładzie dzieciństwa Stanisława Mikołaja Tretera - Kowalczyk, Małgorzata Ewa (Biuletyn Historii Wychowania, 2013)
Stanisław Mikołaj, son of Agnieszka, nee Izbicki, and Stanisław Treter, the king’s chamberlain, was born on 19th November 1776. When he was seven years old it turned out that his mother was mentally ill, most probably suffering from schizophrenia. In the 18th century mental and nervous disorders were very rare, and foreigners visiting Poland even thought they were characteristic of Poles. Certainly, mental disease in a family does not only affect the one who actually suffers from it, it has an impact on each family member and somehow everyone is involved. Agnieszka’s psychosis started with aggressive behaviour towards her family, and especially her son. She would destroy things which either belonged to him or were in some way related to him, she would scream at him, physically and mentally harass him. His father would usually buy the things the boy needed most, such as underwear, clothes and shoes, in well-kept secret. Agnieszka categorically opposed this and even “became stubborn and restless which influenced the atmosphere in this home”. Because of his mother’s disease and its influence on the atmosphere in the family, the boy often felt anxiety and fear, and sometimes even annoyance and despair. In November 1786 Stanisław Treter decided that it would be better if his wife stayed in Warsaw for a while. The atmosphere at home was becoming worse and worse, and their ten-year-old son required systematic and extensive education, while Agnieszka herself needed “professional” care. In the 18th century people who suffered from mental diseases would usually live with their families and be provided with good care and a kind of particular respect, unless they were dangerous to others. However, Agnieszka was completely unpredictable. Her irrepressible aggression was understood by her son as a lack of love and acceptance. He often felt lost and very lonely. His mother’s mental disease did not create supportive conditions for the development of the child’s emotions and mentality. Certainly, like any other child he loved his “Mummy” very much, so parting with her was a very difficult experience for the boy. Disharmony in the Treter family, which was the consequence of Agnieszka’s disease, developed in Stanisław Mikołaj patterns of instability, hostility and neglect. Thus it is not surprising that he became oversensitive, egoistic, combative and aggressive. We learn about Stanisław Mikołaj Treter’s difficult childhood from his father’s notes. In 1785 he decided to write a history of his son’s life and education, and it took him four years to write in 13 letters which are now kept in the Central State Historical Archive of Ukraine in Lvov.